2002
DOI: 10.1103/physrevlett.88.215502
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous LO Phonon Lifetime in AlAs

Abstract: The temperature dependence of the frequencies and linewidths of the Raman-active longitudinal optical (LO) phonons in GaAs and AlAs have been measured. The low-temperature lifetime of the LO phonon in AlAs is found to be 9.7 ps, very close to the corresponding GaAs value of 9.5 ps. This contradicts early theoretical predictions. The agreement between theory and experiment can be restored when the accidental degeneracy between the AlAs LO phonon frequency and a feature in the two-phonon density of states is tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…As expected, we find that the shapes of the distribution of the lifetimes are very similar between GaAs and Si owing to their similar crystal structure and phonon structure (see SI section I for more details). We find that the optical modes (shaded grey in Figure 2a) have relatively short anharmonic decay lifetimes of 10 1 − 10 2 ps, which agrees with previous experiments 58 , and suggest that the anharmonic interactions are the dominant decay process for optical modes in these materials. As the phonon energy decreases into the acoustic regions (shaded red and purple), we find that the lifetimes increase, including extremely large anharmonic lifetimes (> 1 s) for transverse acoustic modes at 7 − 9 meV for GaAs (shaded purple), and 15 − 20 meV for Si.…”
Section: A First-principles Calculationssupporting
confidence: 90%
“…As expected, we find that the shapes of the distribution of the lifetimes are very similar between GaAs and Si owing to their similar crystal structure and phonon structure (see SI section I for more details). We find that the optical modes (shaded grey in Figure 2a) have relatively short anharmonic decay lifetimes of 10 1 − 10 2 ps, which agrees with previous experiments 58 , and suggest that the anharmonic interactions are the dominant decay process for optical modes in these materials. As the phonon energy decreases into the acoustic regions (shaded red and purple), we find that the lifetimes increase, including extremely large anharmonic lifetimes (> 1 s) for transverse acoustic modes at 7 − 9 meV for GaAs (shaded purple), and 15 − 20 meV for Si.…”
Section: A First-principles Calculationssupporting
confidence: 90%
“…Cowley's theory was successfully applied to analyze phonon decay in several temperature-dependent Raman scattering studies of Si, Ge, α-Sn [10], and InN [13], and has revealed subtle effects in the temperature behavior of Raman scattering of compound semiconductors such as AlAs [28] and ZnO [12,29].…”
Section: B Theoretical Model For Anharmonic Decaymentioning
confidence: 99%
“…Considerable progress has been made in recent years in the understanding of the mechanisms which determine phonon linewidths [1][2][3]. The relevant experimental database has been obtained mainly by Raman spectroscopy on samples with diverse isotopic compositions and under hydrostatic stress [4].…”
mentioning
confidence: 99%
“…The line through the points represents the DOS for sums of two phonons with equal q vectors calculated from the ab initio lattice dynamics [8,13]. Raman phonons, at q ' 0, are known to decay mainly into such combinations [1][2][3][4][5]. The frequency range of Zn , where M Zn is the average mass of the zinc atoms, and is nearly independent of the oxygen mass, a conjecture that was checked by changing the isotopic masses in the ab initio calculation.…”
mentioning
confidence: 99%